Character Education or Adab? (An Offer to the Problem of Education in Indonesia)‎ - Sofian hadi; Chairil Anwar; Andrian Syahidu; Iramasan Efendi (Universitas Darussalam Gontor, 2021)
This paper analyzes the implementing concept of curriculum in Indonesia which is consideredable to improve the quality and education system. However, the concept has not showed positive results. On the one hand, integrated character education in the government curriculum has not been able to solve the problem of the moral degradation of the younger generation. This study is a literature review busing qualitative data. The method used is content analysis by analyzing the concept of character education and the concept of adab (ta'dib). As the result, it was found that there were fundamental differences between the concept of character education and the concept of adab. Character education aims to create good citizens (good society), while concept of adab aims to create good people (good individuals). In contrast to that, character education has a fundamental difference to the concept of adab. Furthermore, character education is derived from the Western concept that indicated secular, while the concept of adab is indigenous value from the concept of Islamic education. The concept of adab is considered capable of being an alternative solution for educational theaching in Indonesia because it is in accordance with the objectives of national education which is based on faith (al-Iman), devotion (al-Taqwa) and noble character (al-akhlak al-karimah).